THE INFLUENCE OF WORKSHEET BASED E-LEARNING TOWARD MATHEMATICS LEARNING OUTCOMES IN CLASS X IN SMK MUHAMMADIYAH MAJENANG CILACAP - Muhammad Muliya Al-amien; Suparman Suparman (Universitas Ahmad Dahlan, 2017)
This research was conducted on the ground of the learnings are applied during this tends to be teacher’s centered, many students who are less active, less enthusiastic in learning process. Therefore, it needs a learning model that involves many students makes a student more active. This research aims to determine the Influence Of worksheet based e-learning Toward Mathematics Learning Outcomes Of Student Grade X at SMK Muhammadiyah Majenang Cilacap Of Even Semester in Academic Year 2015/2016. The populations in this research were students of class X RPL SMK Muhammadiyah Majenang. Samples were taken using random sampling techniques derived from class X RPL 3 as an experimental class and class X RPL 1 as the control class. The data collection method used was the test method. Testing instrument using validity test, remainder test, and reliability test. Data were analyzed using a prerequisite analysis test including normality test using Chi-Square formula, homogeneity test by test Bartlett, and hypothesis test with t-test. Based on calculations at the significant level and 58 degrees of freedom, we conclude that : (1) there is a different result of math study that using worksheet based e-learning and conventional. This is indicated by the result of the first test of the hypothesis that (2)learning using worksheet based e-learning is more effective than learning using conventional worksheet. It is shown on the second test of the hypothesis that the test result .